Swarm intelligence and artificial networks of actin filaments - Schumann, Andrew N. (Journal of the Belarusian State University. Sociology, 2019)
In the paper we consider an artificial network of actin filaments as a computational medium from the point of view of computer science. This network is a main factor in keeping the cell shape and in the cell motility. The matter is that the actin filament network is responsible for the cell deformation, e. g. for the cell division into two cells, for growing pseudopodia for feeding. Meanwhile, actin filaments assemble and disassemble in course of time. As a consequence, we face the permanent appearing and disappearing filaments. This network possesses algorithms which are realizable in any swarm behaviour. Its examples are as follows: insect swarm, bird flock, horse herd, fish school. From the standpoint of behaviourism, this behaviour is social. However, from the standpoint of symbolic interactionism, it is not. In the paper there are given examples of swarm (non-social collective) behaviour of human beings.
Keywords: swarm intelligence; actin filaments; swarm behaviour; social behaviour